(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
this paper compares syntagmatic and paradigmatic relations in English and Uzbek. English, an analytic language with fixed SVO word order and limited inflection, contrasts with Uzbek, an agglutinative language with rich suffixation and flexible word order. The study examines phonetic, morphological, syntactic, and lexical subsystems. English shows complex syllable structures and rigid syntactic patterns, while Uzbek features vowel harmony and extensive morphological paradigms. Differences in collocations and substitution sets reflect typological contrasts. The analysis highlights how structural typology shapes linguistic organization, drawing on Saussurean theory and modern Uzbek linguistic research.